EXAMINING THE EFFECTS OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: EVIDENCE FROM A PUBLIC LAW ENFORCEMENT INSTITUTION IN INDONESIA - Apriliani E. Permatasari; Yenny Maya Dora (Branding: Jurnal Manajemen dan Bisnis, 2026)
Employee performance has become a strategic concern in public organizations as governments pursue bureaucratic reform to improve accountability, service quality, and organizational effectiveness. Although transformational leadership and work environment are widely recognized as key determinants of employee performance, empirical evidence from law enforcement and public prosecution institutions remains scarce, particularly in emerging economies. This study investigates the influence of transformational leadership and work environment on employee performance within Indonesia's public prosecution service, using the West Java Provincial Prosecutor's Office as the research setting. A quantitative cross-sectional design was employed by surveying 200 employees selected through proportionate stratified random sampling from a population of 400 employees. Data were analyzed using multiple linear regression with IBM SPSS 27. The findings reveal that both transformational leadership and work environment significantly enhance employee performance. Transformational leadership exerts the strongest influence (β = 0.471, p < 0.001), followed by work environment (β = 0.362, p < 0.001). Together, these variables explain 45.8% of the variance in employee performance (R² = 0.458), indicating that leadership behaviors and supportive workplace conditions constitute important organizational resources for improving employee outcomes. The study extends the transformational leadership literature by providing empirical evidence from an underexplored public-sector context and demonstrates the complementary role of workplace conditions in enhancing employee performance. These findings offer practical insights for public managers seeking to strengthen organizational effectiveness through leadership development and improvements in the work environment, thereby supporting the implementation of bureaucratic reform.